Pediatric and Adolescent Forearm Fractures: Current Controversies and Treatment Recommendations. Issue 11 (November 2016) - Pace, James Lee
Abstract : Pediatric and adolescent forearm fractures continue to present treatment challenges. Despite high-level evidence to the contrary, traditional guidelines for nonsurgical treatment have been challenged in favor of surgical intervention, but it is unclear if this results in improved outcomes. Recent evidence suggests that certain open fractures in children may be successfully treated nonsurgically. Good results have been achieved with closed reduction and appropriate casting and clinical follow-up. Further research investigating functional outcomes into adulthood is needed.